Cholesterol dependent downregulation of mouse and human apical sodium dependent bile acid transporter (ASBT) gene expression: molecular mechanism and physiological consequences. Issue 9 (16th February 2006) - Thomas, C; Landrier, J-F; Gaillard, D; Grober, J; Monnot, M-C; Athias, A; Besnard, P
Abstract : Background and aims: Faecal bile acid elimination greatly contributes to cholesterol homeostasis. Synthesised from cholesterol in the liver, bile acids are actively reclaimed in the ileum by the apical sodium dependent bile acid transporter (ASBT). Although the expression level of ASBT affects body cholesterol balance, the impact of cholesterol on ASBT gene expression remains unclear. In this study, the effect of cholesterol on ASBT expression and ileal bile acid uptake was explored in vivo and in vitro. Methods: ASBT gene expression was assessed by real time quantitative polymerase chain reaction and northern or western blotting, or both, in mice subjected to a 2% cholesterol diet for two weeks, in mouse ileal explants, or in human enterocyte-like Caco-2 cells cultured in sterol enriched or depleted media. Bile acid uptake was determined by measuring [ 3 H]-taurocholic acid influx into in situ isolated ileal loops from mice or into differentiated Caco-2 cells. Molecular analysis of mouse and human ASBT promoters was undertaken with reporter assays, site directed mutagenesis, and electrophoretic mobility shift assays. Results: In mice, cholesterol enriched diet triggered a downregulation of ASBT expression (mRNA and protein), a fall in ileal bile acid uptake, and a rise in the faecal excretion of bile acids. This effect was direct as it was reproduced ex vivo using mouse ileal explants and in vitro in differentiated Caco-2 cells. Conclusions: This regulation, which involves an original partnership between SREBP-2 and HNF-1α transcription factors, affects ileal bile acid recycling and thus might participate in the maintenance of body cholesterol homeostasis.